Model Pendidikan Gerak untuk Meningkatkan Physical-Self-Concept pada Pendidikan Jasmani di Sekolah Dasar - Astuty, Safithry 'Indy; Slamet, Suherman; Wibowo, Ricky (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
This study is motivated by the lack of students' understanding of the concept of physical self (Physical Self-Concept) in physical education which is still low, and many students who do not look at physical performance, physical appearance, and weight control in physical activities and educators must apply to a movement education model so that students can understand the Physical Self-Concept on students' physical abilities. The purpose of the study is to determine the effect through the application of the movement education model to improve the Phyical Self-Concept in physical education in elementary schools. The research method uses Classroom Action Research with 2 cycles, in one cycle consisting of 2 actions. In the study conducted at SDN 032 Tilil in Bandung City, with a sample of class III A students totaling 29 students (13 male students, 16 female students). The instrument used is the CPSS (Children's Physical Self Scale) on students according to their abilities and learning outcomes in the movement education model. Based on the results of study data, that students can carry out the learning process through physical self-concept in physical education in elementary schools with the application of the movement education model can be increased.AbstrakStudi ini dilatarbelakangi oleh kurangnya pemahaman siswa akan konsep diri terhadap fisik (Physical Self-Concept) pada pendidikan jasmani yang masih rendah, dan banyak siswa yang tidak melihat akan performa jasmani, penampilan jasmani, dan kontrol berat badan pada aktivitas jasmani dan pendidik harus menerapkan pada model pendidikan gerak agar siswa dapat memahami tentang Physical Self-Concept pada kemampuan jasmani siswa. Tujuan dari penelitian yaitu mengetahui pengaruh melalui penerapan model pendidikan gerak untuk meningkatkan Phyical Self-Concept pada pendidikan jasmani di Sekolah Dasar. Metode penelitian menggunakan Penelitian Tindakan Kelas dengan 2 siklus, dalam satu siklus terdiri dari 2 tindakan. Pada penelitian dilakukan di SDN 032 Tilil Kota Bandung, dengan sampel peserta didik kelas III A yang berjumlah 29 siswa (13 siswa laki-laki, 16 siswa perempuan). Instrumen yang digunakan yaitu CPSS (Children’s Physical Self Scale) pada siswa sesuai dengan kemampuan yang mereka miliki dan hasil belajar pada model pendidikan gerak. Berdasarkan hasil data studi, bahwa siswa dapat melaksanakan proses pembelajaran melalui physical self-concept pada pendidikan jasmani di sekolah dasar dengan penerapan model pendidikan gerak dapat meningkat.